862 Process Mapping of 3D Printing for Complex Limb Problems. (19th August 2022) - Quang, J; Ferguson, D
Abstract: Introduction: Difficult limb problems such as complex trauma or re-presentation following orthopaedic revision surgeries can present substantial planning and technical challenges. 3D-printed models built from patient-specific CT scans facilitate creative thinking, problem solving and decision making to find better operative solutions. This quality improvement project aims to map the process of using 3D printers to solve orthopaedic problems. Method: Stakeholders, including a Consultant Trauma & Orthopaedic surgeon and the Medical Physics team were interviewed to formalise the full structure of their role from start to end, with the support of the Trust's Improvement Team and Innovation Team. A visual representation of the process map was produced using SmartDraw software. Feedback was received from stakeholders and a second cycle of process mapping was completed. Results: The process map included the chronological steps of the project, the interaction between different roles and the stages of 3D printing. A database template was produced as a shared OneNote, allowing the tracking of each model production. Stakeholders found the map useful for anticipating problems and considering the future process and providing a framework of implementing innovation within the NHS. Discussion: Unique implants cost the NHS significantly more money than batch-made products. Introduction of 3D models into pre-operative planning allow surgeons to utilise readily available solutions instead of custom, single-use implants, which can be cost saving and prevents unnecessary wastage. The project trialled operations on models, facilitated patient explanations and provided an educational tool. Future aims include roll-out to other specialties and Trusts, encouraging collaboration towards a sustainable internal economy.